Proyek Lintas Batas Administrasi: Analisis Partisipasi Publik dalam Proses Perencanaan Ibu Kota Negara Republik Indonesia - Rizkiana Sidqiyatul Hamdani (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2020)
Administrative Transboundary Project: Public Participation Analysis in Indonesia’s New Capital City Planning Processes The Central Government of the Republic of Indonesia once again formulated a plan for moving the National Capital (IKN). The existing government centers in DKI Jakarta Province will be moved to North Penajam Paser Regency and Kutai Kartanegara Regency in East Kalimantan Province. As the progress of planning and preparation for the implementation of this discourse, public opinion is still dominated by negative sentiment, one of the escalated issues is public participation. As the core of democracy, public participation in decision making in the Republic of Indonesia is a necessity. This study intends to review the IKN planning process that has been carried out from the perspective of the participation ladder theory. Descriptive qualitative method used by analyzing electronic news (understanding chronological stories of the project) and media social data (public participation and perception). Comparing those data with previous researches were done to increase depth of analysis. The result showed that participatory regional planning process in IKN project is in the degree of tokenism or symbolism. This is hoped to provide evaluation in the implementation of the capital city relocation project, thus could contribute in creating more inclusive planning processes in further implementation stages.